1985
DOI: 10.1159/000287855
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Measures of Alexithymia: What Do They Measure

Abstract: Previous studies have shown that measurement of verbal affective expression is influenced by the method used for obtaining speech samples, thereby supporting a situation-dependent, or state concept of alexithymia. In this study monadic speech samples obtained from 20 psychoneurotic and 20 psychosomatic patients, using selected thematic apperception test (TAT) cards, were examined using different methods of content analysis. Although no differences were found with the Gottschalk-Gleser anxiety, hostility outwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…Findings of the study regarding the role of socioeconomic status as measured by educa tion agree with others in favor of no relation ship between the alexithymie traits and level of education [10][11][12].…”
Section: Demographic Variables and Alexithymiasupporting
confidence: 80%
See 2 more Smart Citations
“…Findings of the study regarding the role of socioeconomic status as measured by educa tion agree with others in favor of no relation ship between the alexithymie traits and level of education [10][11][12].…”
Section: Demographic Variables and Alexithymiasupporting
confidence: 80%
“…In the cases where inter-rater reliability was inacceptably low (r = 0.30) [10], it was reported that the assessment interview proce dure was questionable. In this case, the inter viewers held separate interviews of the sub ject, then rated the subject by their own inter view, allowing much room for inconsistency in the content of the interview and interview er's style.…”
Section: Inter-rater Reliability O F the Biqmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, alexithymia is understood as a deficit in emotional and cognitive regulatory processes that are required for symbolic function, fantasy and empathy. Early studies, prior to the development of a psychometrically sound instrument, suggested a high prevalence of alexithymia in UC compared to irritable bowel syndrome [50]and psychoneurotic controls [51]and decreased verbal content on emotional tasks in UC and CD patients [52, 53]. A recent case-control study of 112 IBD patients using the validated Toronto Alexithymia Scale found a rate of alexithymia of 35.7%, significantly greater than the rate in healthy controls of 4.5% [54], and these alexithymia scores appear to be stable over time [55].…”
Section: Coping In Ibdmentioning
confidence: 99%
“…Indeed, in a study comparing alexithymia in IBD patients and psychoneurotic patients, Taylor et al [ 16] found unacceptable interrater agreement on the BIQ and no significant difference in the mean BIQ scores of the two patient groups. Nonetheless, using projective test measures, Taylor et al [16][17][18] did find that IBD pa tients were less able to verbalize emotions than psychoneurotic patients, and also less able to modulate emotions, thus providing partial support for an association between alexithymia and IBD.…”
Section: Introductionmentioning
confidence: 99%